First-passage times for pattern formation in nonlocal partial differential equations - Caceres Garcia Faure, Manuel Osvaldo; Fuentes, Miguel Angel (American Physical Society, 2015)
Fil: Caceres Garcia Faure, Manuel Osvaldo. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina